Introducing Registered Reports at Language Learning: Promoting Transparency, Replication, and a Synthetic Ethic in the Language Sciences. Issue 2 (3rd March 2018) - Marsden, Emma; Morgan‐Short, Kara; Trofimovich, Pavel; Ellis, Nick C.
Abstract: The past few years have seen growing interest in open science practices, which include initiatives to increase transparency in research methods, data collection, and analysis; enhance accessibility to data and materials; and improve the dissemination of findings to broader audiences. Language Learning is enhancing its participation in the open science movement by launching Registered Reports as an article category as of January 1, 2018. Registered Reports allow authors to submit the conceptual justifications and the full method and analysis protocol of their study to peer review prior to data collection. High‐quality submissions then receive provisional, in‐principle acceptance. Provided that data collection, analyses, and reporting follow the proposed and accepted methodology and analysis protocols, the article is subsequently publishable whatever the findings. We outline key concerns leading to the development of Registered Reports, describe its core features, and discuss some of its benefits and weaknesses.